A METHODOLOGY FOR FORMING CHILDREN'S SCIENTIFIC WORLDVIEW BASED ON EMPIRICAL EXPERIENCES FROM THE PRESCHOOL EDUCATIONAL PROCESS (Global Conference on Multidisciplinary Research and Innovation, 2026)
The paper presents a methodology for shaping preschool children’s scientific worldview through empirical experiments. It proposes integrating observation, hands-on experimentation, comparison, and drawing conclusions into everyday learning activities. Pedagogical conditions, assessment criteria, and practical recommendations are substantiated with applied examples suitable for preschool settings.
Keywords: Empirical experiment; observation; preschool education; scientific worldview; inquiry-based activity; questioning; assessment criteria.